Alelopathic activity of extracts of Ocotea puberula (Rich.) Nees on the germination and initial growth of lettuce - Bonini, Edicléia Aparecida; Jungbluth, Daiana; Ascari, Jociani (Scientia Agraria Paranaensis, 2021)
The interest in the exploration of compounds from the secondary metabolism is seen as a strategic alternative in agriculture, even for the control of invasive plants. The objective of this work was to measure the allelopathic activity of extracts CHCl3 and AcOEt from the leaves of O. puberula on the germination of lettuce. The ethanolic extract was obtained from the dried and milled leaves. The crude extract was solubilized in ethanol and acidified (hydroalcoholic fraction). The C6H14 fraction was obtained by liquid-liquid extraction of the hydroalcoholic fraction, the same procedure was used to extract the AcOEt fraction. The hydroalcoholic fraction was basified and extracted with CHCl3. The chemical profile of the obtained fractions was analyzed by Thin Layer Chromatography using specific revelators that confirmed the presence of alkaloids as majority compounds in AcOEt and CHCl3 fractions. The fractions were evaluated for allelopathic potential on lettuce cypselas at 0.8 g mL‑1, 0.4 g mL-1 and 0.2 g mL-1. In germination tests the germination parameters analyzed were: germination percentage (% G) and germination speed index (IVG). The results indicated significant changes in the %G, IVG and root growth (CR) of the lettuce seeds and seedlings. The ethanolic extract of leaves of O. puberula showed allelopathic influence on the species L. sativa. Both the AcOEt and CHCl3 fractions reduced the germination rates evaluated, and the latter indicated a dose-response inhibition between the treatments applied.